DEVELOPMENT OF HYBRID ENCRYPTION METHOD USING AFFINE CIPHER, VIGENERE CIPHER, AND ELGAMAL ALGORITHM TO SECURE TEXT MESSAGES IN DATA COMMUNICATION SYSTEM - SINAMBELA, RIFDAHTUL GHINAA; Fauzi, Achmad (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
With the development of technological advances in this day and age, it definitely requires a security system on messages and data. The way to maintain the security of data, messages or information requires a branch of science in its application, one of which is the algorithm or cryptography method. In its application, it requires more than one stage of the security process, because data security can be done by combining methods in its security techniques. This research aims to develop encryption methods using Affine Cipher, Vigenere Cipher, and ElGamal Algorithm to secure text messages. Affine cipher, Vigenere cipher and ElGamal are cryptography that can encrypt and decrypt text messages. Encryption is changing the message or plaintext into an unreadable message or ciphertext, on the other hand, decryption changes the ciphertext or message that initially cannot be read into a message that can be read or plaintext back in its original form. The result of this research is the development stage by doing three encryption and decryption processes. For the first encryption process using Affine Chiper which produces the initial ciphertext, then re-encrypted using Vigenere Cipher, then the previous encryption results are carried out ElGamal encryption which produces the final ciphertext. Conversely, the decryption process is first on ElGamal, then Vigenere Cipher, and finally Affine Cipher whose decryption results in plaintext back in the form of the initial text message. So that by developing and combining three algorithm methods can increase the security of information and text messages.